Human Endothelial Cell-derived Nuclear Proteins that Recognise Polymorphic DNA Elements in the von Willebrand Factor Gene Promoter Include YY1 - Costa, Magdaline; Grant, Peter J.; Rice, Gillian I.; Futers, Simon T.; Medcalf, Robert L. (Thrombosis and Haemostasis, 2001)
Four common base-change polymorphisms have been found in the von Willebrand factor gene promoter: (-1793 C/G, -1234 T/C, -1185 G/A and -1051 A/G). All four polymorphisms are in strong linkage dis-equilibrium and recent reports have indicated these polymorphisms are associated with plasma vWF:Ag levels suggesting that one or more of these elements influence regulation of the vWF gene. We report that human endothelial cell-derived trans-acting factors display allelic preferences in binding activity to each polymorphic site. The common A allele variant of the –1051 polymorphism and the rarer A allele variant of the –1185 polymorphism provided specific binding of nuclear proteins. The G allele counterpart of these two variants did not produce any complex formation indicating that the nucleotide substitution at these positions alters the DNA binding ability of nuclear factors. The two alleles of the –1234 polymorphism produced two complexes with a similar migration pattern however stronger binding was found to the common T variant of this allele. Two specific complexes associated with the rarer G allele of the –1793 polymorphism, but only one associated with the C allele. Supershift experiments revealed that the trans-acting factor YY1 recognised the slower migrating complex formed on the –1234 T/C and the –1051 A polymorphic sites with a strong binding preference for the –1234 T allele variant. The identification of YY1 as a component of the factors that recognise these elements suggests that this ubiquitous nuclear protein may play a role in the regulation of the vWF promoter.
Keywords: vWF promoter polymorphism; YY1; endothelial cell